Nutrient management for basmati rice (oryza sativa L) in wetlands - Sindu M S (Department of Agronomy, College of Agriculture, 2002)
A field experiment was conducted at the Instructional Farm, College of Agriculture, Vellayani from September 2001 to January 2002 to derive an optimum package for nutrient management for basmati rice in wetland condition. The experiment was laid out in factorial RBD with three replications. The treatments consisted of three levels of N (60, 90 and 120 kg N ha"), two sources of N (SI: SO per cent N as FYM and SO per cent N as chemical fertilizer and S2 : SO per cent N as vermicompost and SO per cent N as chemical fertilizer), two NPK ratios (2 : 1 : 1 and 2 : 1 : I.S) and an absolute control thereby forming 13 treatment combinations. Results of the experiment revealed that the effect of both N levels and NPK ratios had significant influence on most of the biometric and yield attributing characters and yield of basmati rice. Nitrogen @ 120 kg ha-I and NPK ratio of 2 : 1 : I.S were found significantly superior to lower levels. Eventhough the effect of sources of N was significant on plant height and dry matter production, the effect was not visible on the yield attributing characters and yield of the crop. A significant linear increase in grain yield was recorded upto 90 kg N ha-I , and thereafter the increase in grain yield was marginal. But the straw yield increased linearly with increase in N level and was also significantly influenced by the sources of nitrogen. NPK ratio of 2 : 1 : I.S recorded higher grain and straw yield. Nitrogen @ 120 kg ha-I and NPK ratio of 2 : I : I.S produced the highest grain protein content. The cooking time of grains increased with increase in N level. Nitrogen @ 120 kg ha-I and NPK ratio of 2 : I : I.S recorded the highest uptake of nutrients. Use of vermicompost for substituting 50 per